2022
DOI: 10.1017/s0954579421001462
|View full text |Cite
|
Sign up to set email alerts
|

Improving parenting, child attachment, and externalizing behaviors: Meta-analysis of the first 25 randomized controlled trials on the effects of Video-feedback Intervention to promote Positive Parenting and Sensitive Discipline

Abstract: Improving parenting, child attachment, and externalizing behaviors: Meta-analysis of the first 25 randomized controlled trials on the effects of Video-feedback Intervention to promote Positive Parenting and Sensitive Discipline (VIPP-SD). VIPP-SD combines support of parental sensitive responsiveness with coaching parents in sensitive limit setting. Here, we present meta-analyses of 25 RCTs conducted with more than 2,000 parents and caregivers. Parents or children had various risks. We examined its effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 96 publications
(115 reference statements)
5
52
1
Order By: Relevance
“…Contrary to our expectations, the VIPP-SD did not influence parental sensitivity as assessed in the present study. Although this is in line with the findings of the Euser et al (2021) study, it is not what we had expected based on meta-analytic findings on the effectiveness of the VIPP-SD program (Juffer et al, 2017; Van IJzendoorn et al, in press). It might be that the intervention indeed failed to have an effect on sensitivity.…”
Section: Discussionsupporting
confidence: 78%
“…Contrary to our expectations, the VIPP-SD did not influence parental sensitivity as assessed in the present study. Although this is in line with the findings of the Euser et al (2021) study, it is not what we had expected based on meta-analytic findings on the effectiveness of the VIPP-SD program (Juffer et al, 2017; Van IJzendoorn et al, in press). It might be that the intervention indeed failed to have an effect on sensitivity.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, Smaling et al ( 2016 ), the only study on prenatal PRF we are aware of, found a specific association between maternal prenatal PRF and sensitivity only in teaching situations, which may resemble more of our measure of structuring. One potential reason for this unexpected lack of findings was perhaps that the PGT intervention used in our study was not directly focused on increasing maternal sensitivity, lacking the most effective means, such as the use of video feedback (see van IJzendoorn et al, 2022 ). The current PGT interventions instead concentrated more around supporting maternal abilities to regulate themselves and their infants, which was also evident in more effectiveness for intrusiveness and hostility rather than sensitivity (Belt et al, 2012 ).…”
Section: Discussionmentioning
confidence: 93%
“…To conclude, mothers with prenatal SUD need treatments that are multi-professional and comprehensive and should be started during pregnancy to prevent both fetal exposure and the development of dyadic interaction problems (Flykt et al, 2021 ). The parenting component of treatments should ideally include the following elements: First, direct support of sensitivity toward the infant (such as with the use of video feedback, van IJzendoorn et al, 2022 ) is vital. Second, the mothers need help in mentalizing the infant and their parenting.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analytic evidence has shown that the Video-feedback Intervention to promote Positive Parenting and Sensitive Discipline (VIPP-SD) is effective in increasing parental sensitivity, parental sensitive discipline, and child attachment security [ 1 , 2 ]. Parenting and attachment are important factors in the development and continuity of children’s stress regulation and externalizing behavior problems [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, parents learn to see even subtle signals of proximity-seeking behavior in their child and to react promptly and adequately, which should help decreasing child stress levels [ 1 ]. Although the effects of the VIPP-SD on parental sensitivity and secure attachment have been supported in several randomized trials and confirmed in a meta-analysis of 25 randomized controlled VIPP-SD studies, the evidence for the effects of VIPP-SD on children’s externalizing behavior remains inconclusive [ 2 ]. The most recent and largest pragmatic randomized trial conducted within the context of the British National Health Service (NHS) including more than 300 families with toddlers at risk for externalizing problems showed a significant effect of VIPP-SD on conduct problems [ 9 ].…”
Section: Introductionmentioning
confidence: 99%